Interrelationship between principals' transformational leadership style, teachers' job satisfaction, and school effectiveness in secondary schools of Lagos state, Nigeria - Moshood, Yusoff Adeola (2020)
Principal transformational leadership style together with teacher’s job satisfaction have proven to be an important decisive factor for secondary schools to be seen as effective. Presently, there is a dearth of studies on principals’ transformational leadership style and job satisfaction of teachers with regards to secondary schools' effectiveness in Lagos state. Thus, the current study is aimed at exploring the linkage between school principals’ transformational leadership style, teachers’ job satisfaction, and their relationship to school effectiveness as perceived by the school teachers. The study further investigates the level of Principals’ transformational leadership style, teachers’ job satisfaction, and school effectiveness and determined the contributions of independent variables to school effectiveness. The study was designed as correlational research using validated self-administered questionnaires. The total sample size distribution of 405 questionnaires was obtained using Cochran formulae to determine the sample size. However, 91.8% of the total distributed questionnaires were valid and returned by the respondents. To achieve the accuracy of the results, data were analyzed using descriptive statistical tools to determine the descriptive analysis of the level of school principals’ transformational leadership, teachers’ job satisfaction, and school effectiveness. Data obtained from the questionnaire were analyzed using SPSS version 23. Pearson correlation and multiple regression analysis were employed to determine the relationship between the principals’ transformational leadership, teachers’ job satisfaction, and school effectiveness. From the descriptive analysis, it was observed that the three variables in this study were at a moderate level. The result of the correlation analysis showed that transformational leadership, job satisfaction, and school effectiveness were all significantly related. Furthermore, Regression analysis indicated that the transformational leadership style appeared to be the best contributor to school effectiveness. In conclusion, the findings of this study can be beneficial to stakeholders and school administrators to improve on practicing transformational leadership style, teacher’s wellbeing through better pay, promotions, ii training, and retirements benefits to positively affect and improve the effectiveness of secondary schools in Lagos State, Nigeria.